Herpesvirus Infection in Development of Hemorrhagic Vasculitis in Children (Literature Review) - A. Mamyrbayeva, M.; H. Isanguzhina, Zh.; B. Shilmanova, A.; M. Nurgaliev, N.; K. Ismambetova, G. (International Journal of Engineering and Technology, 2018)
The authors conducted a systematic review of the literature published in the last fifteen years. The results of the literature review showed that the role of herpesvirus infection in the occurrence of primary vasculitis is not excluded. In the works of Kazakhstan and foreign researchers who consider that ability of viruses to cytopathic effect is important for herpesvirus infection, herpes simplex infection is not excluded as a leading factor in the development of HV. In this regard, the study of the etiology of HV will help to reach a new therapeutic level of the disease. Consequently, the problem of HV is of scientific interest and practical importance. Â Â Â